TUMOR MICROENVIRONMENT REGULATION BY HYPOXIA-INDICIBLE FACTORS (HIFs), AND p53 FAMILY PROTEINS - Petrova, V S; Barlev, N A (T͡S︡itologii͡a, 2017)
Except affecting cancer cells, hypoxia and HIF-dependant signaling lead to changes in tumor microenvironment, which plays an important role in cancer progression. Tumor microenvironment modification can influence the immune response, tumor growth and metastases. On the other hand it is well known that more than half cases of all cancers are characterized by mutation in the gene encoding tumor suppressor p53. Inactivation of p53 is necessary for cancer progression on the late stages. Therefore an existence of reciprocal regulation between HIF proteins family and p53 proteins family may be an important factor determining course of disease. In this review we attempt to make a general picture of changes that take place in different components of tumor microenvironment in response to hypoxia and HIFs and impact of the p53 family genes on these processes.